Evidence for changes in historic and future groundwater levels in the UK. (February 2015) - Jackson, Christopher R.; Bloomfield, John P.; Mackay, Jonathan D.
We examine the evidence for climate-change impacts on groundwater levels provided by studies of the historical observational record, and future climate-change impact modelling. To date no evidence has been found for systematic changes in groundwater drought frequency or intensity in the UK, but some evidence of multi-annual to decadal coherence of groundwater levels and large-scale climate indices has been found, which should be considered when trying to identify any trends. We analyse trends in long groundwater level time-series monitored in seven observation boreholes in the Chalk aquifer, and identify statistically significant declines at four of these sites, but do not attempt to attribute these to a change in a stimulus. The evidence for the impacts of future climate change on UK groundwater recharge and levels is limited. The number of studies that have been undertaken is small and different approaches have been adopted to quantify impacts. Furthermore, these studies have generally focused on relatively small regions and reported local findings. Consequently, it has been difficult to compare them between locations. We undertake some additional analysis of the probabilistic outputs of the one recent impact study that has produced coherent multi-site projections of changes in groundwater levels. These results suggest reductions in annual and average summer levels, and increases in average winter levels, by the 2050s under a high greenhouse gas emissions scenario, at most of the sites modelled, when expressed by the median of the ensemble of simulations. It is concluded, however, that local hydrogeological conditions can be an important control on the simulated response to a future climate projection.